Field screening and genetic mapping of wheat blast resistance for a panel of common wheat from Bangladesh - Md. Farhad; Xinyao He; Hirokazu Handa; Muhammad Rezaul Kabir; Krishna Kanta Roy; Felix Marza; Masahiro Kishi; Soichiro Asuke; Pawan K. Singh (PLoS ONE, 2026)
Wheat blast, caused by Magnaporthe oryzae pathotype Triticum (MoT), is a rapidly emerging disease threatening wheat production in South Asia and beyond. To identify novel sources of resistance and dissect the underlying genetic architecture, a genome-wide association study (GWAS) was conducted using 432 diverse Bangladeshi wheat genotypes phenotyped across 14 multi-environment trials. Disease severity varied widely, with most genotypes exhibiting high susceptibility under favourable environments, although a few showed consistent resistance across locations. Genotyping of the wheat panel using ddRAD-seq revealed moderate population structure and diverse resistance allele distribution. GWAS using six different models identified a total of 1,121 significant SNPs distributed across multiple chromosomes. The 2NS translocation and known resistance genes ( Rmg8 , Rwt3 , Rwt4-1B , Rwt4-1D ) were unevenly distributed across the panel. Based on linkage disequilibrium (LD), the significant markers were grouped into 45 quantitative trait loci (QTL) associated with wheat blast resistance, including the 2NS/2AS translocation. These QTLs either coincide with known blast resistance loci or represent potentially novel ones. These findings enhance the understanding of wheat blast resistance and provide valuable markers and candidate genotypes for resistance breeding aimed to mitigate the threat of wheat blast under changing climates.